Using NLP to prove the Unified theory of acceptance and use of technology (UTAUT2) - Neves, Francisco Manuel Carujo Tavares das (2023)
Project Work presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics